PERANCANGAN BEL SEKOLAH OTOMATIS BERBASIS ARDUINO PADA SDN 32 BARABBA KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Mila Aprilianti (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2020)
This research aims to: (1) Design an Arduino-based automatic school bell, (2) Implement an Arduino-based automatic school bell, (3) the effectiveness of the proposed system.This research uses the Action Research method (action research) is to apply fact finding to solving problems in social situations with a view to improving the quality of actions taken in it, which involves collaboration and collaboration of researchers, practitioners, and lay people In this study it can be concluded that the ARDUINO-based automatic school bell is equipped with a Real time Clock (RTC) DS3231 as a timer and a mini MP3 Player that is able to play sound file formats so information conveyed through the bell can be in the form of sound using English and Indonesian. With the ability to play sound files in mp3 format, the information conveyed through the bell can be easily understood by all students (i) and teachers at school.